Absorção de nutrientes em cultivares de gérbera cultivada em vaso - Ludwig, Fernanda [UNESP]; Fernandes, Dirceu Maximino [UNESP]; Guerrero, Amaralina C [UNESP]; Villas Boas, Roberto Lyra [UNESP] (Associação Brasileira de Horticultura, 2013)
The analysis of the uptake of nutrients is important for understanding the nutritional requirements of a cultivar during its development and identifies periods of increased demand, which allows scheduling fertigation. Nevertheless, the information is limited for gerbera. Thus, the present study was conducted to determine the uptake of potted gerbera cultivars Cherry and Red conducted in substrate in a crop cycle in the period August-October 2008. The experiment was carried out in a greenhouse in a randomized block split plot with four replications. The plots were composed by cultivars and subplots by dates of collection. During the development of the plants, the content and accumulation of macro and micronutrients was assessed in plant tissue of the shoots. The macronutrients were accumulated in the following order: K>N>Ca>Mg>P>S (524, 334, 119, 47, 42, 21 mg plant-1). The micronutrients were accumulated in the following order: Fe>Mn>B>Zn>Cu (7897, 1505, 801, 384,63 µg plant-1). The reproductive was the period of greatest uptake of nutrients, except for Fe.

A análise da absorção de nutrientes ao longo do ciclo da cultura é importante para o conhecimento das necessidades nutricionais nas épocas de maior demanda e programar a fertirrigação, sendo escassas as informações para gérbera. Assim, o objetivo foi quantificar a absorção das cultivares de gérbera de vaso Cherry e Red, conduzidas em substrato em um ciclo de cultivo no período de agosto a outubro de 2008. O experimento foi realizado em casa-de-vegetação com delineamento em blocos ao acaso, com parcela subdividida e 4 repetições. As parcelas foram compostas pelas cultivares e subparcelas pelas datas das coletas. Durante o desenvolvimento da cultura foram determinadas a fitomassa seca, o teor e acúmulo de nutrientes no tecido vegetal da parte aérea das plantas. Os macronutrientes foram absorvidos na seguinte ordem: K>N>Ca>Mg>P>S (524, 334, 119, 47, 42, 21 mg planta-1). Os micronutrientes foram absorvidos na seguinte ordem: Fe>Mn>B>Zn>Cu (7897, 1505, 801, 384, 63 µg planta-1). O período reprodutivo foi o de maior acúmulo de nutrientes, exceto para o Fe.
Nutrient uptake in potted gerbera cultivars
Keywords: Gerbera jamesonii; cultivo sem solo; nutrição de plantas; Gerbera jamesonii; soilless culture; plant nutrition